RF installation for the grain disinfestation - Zajtzev, B.V.; Bomko, V.A.; Rashkovan, V.M.; Kobetz, A.F.; Rudiak, B.I.; Bazyma, L.A.; Basteev, A.V.; Lesnykh, M.S.; Mishchenko, O.O.; Zhuravlev, V.G.; Marinina, E.D. (Вопросы атомной науки и техники, 2001)
The ecologically pure method of grain product disinfestations through the grain treatment with the RF electric field is described. The experimental data obtained showed that with strengths of the electrical RF field of E=5 kV/cm and frequency of 80 MHz the relative death rate is 100%. The time of the grain treatment in this case is 1 sec. The pulses with a duration of 600 μs and repetition rate of 2 Hz were used, the duration of the front was 10 μs. The schematic layout of installation with a productivity of 50 tones/h and power of 10 kW is given.